Solution :
We have to tackle this problem by forming a recurrence relation. Let T(n) be number of leaves in a tree having n internal nodes. We have to somehow relate T(n) to T(n-1).
Consider a tree with n = 1. This tree will be having exactly k Leaves.
Try creating a tree with 2 internal nodes from the above tree. We have to make one leaf node an internal node and while doing this, we are getting more k leaves. Therefore, number of leaf nodes in the newly constructed tree will be one less than original tree as we have changed one leaf to internal node plus k (Newly converted node has now spawn k more leaves).
Thus, T(n) = T(n-1) - 1 + k = T(n-1) + k -1
= T(n-2) + 2*(k-1) Solving By Substitution Method
= T(n-3) + 3*(k-1)
.
.
.
= T(n-(n-1)) + (n-1)*(k-1)
= T(1) + (n-1)*(k-1)
= k + (n-1)*(k-1) Forming Base Case : T(1) = k
= n(k – 1) + 1
So C) is correct.